Obiektywne możliwości monitorowania postępów terapii tkanek miękkich w rehabilitacji z zastosowaniem EMG = Objective possibilities of monitoring the progress of a treatment of soft tissues in the rehabilitation with the EMG application - Joanna Michalik (Kazimierz Wielki University, 2016)
Michalik Joanna. Obiektywne możliwości monitorowania postępów terapii tkanek miękkich w rehabilitacji z zastosowaniem EMG = Objective possibilities of monitoring the progress of a treatment of soft tissues in the rehabilitation with the EMG application. Journal of Education, Health and Sport. 2016;6(8):554-559. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60952 http://ojs.ukw.edu.pl/index.php/johs/article/view/3772 https://pbn.nauka.gov.pl/sedno-webapp/works/744823     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 22.08.2016.     Obiektywne możliwości monitorowania postępów terapii tkanek miękkich w rehabilitacji z zastosowaniem EMG Objective possibilities of monitoring the progress of a treatment of soft tissues in the rehabilitation with the EMG application   Joanna Michalik¹   1 NZOZ Sanus, Lublin     Autor do korespondencji: Joanna Michalik Niepubliczny Zakład Opieki Zdrowotnej "SANUS", ul Magnoliowa 2, 20-144 Lublin JoannaMichalik21@wp.pl Tel. 600 065 151     Streszczenie Elektromiografia to pomiar sygnału elektrycznego powiązanego ze skurczem mięśnia. Jest uznawana za obiektywną metodę służąca do rejestracji potencjałów mięśni powierzchownych. Z powodu powtarzalności i możliwości porównywania badań elektrofizjologicznych używana jest w postępowaniu diagnostycznym oraz kontrolowaniu przebiegu schorzenia i efektywności leczenia. Celem naszej pracy było zaprezentowanie przeglądu literatury. Niniejsze badania pokazują jak elektromiografia powierzchniowa przydatna jest w obiektywnej ocenie  skuteczności terapii tkanek miękkich.   Słowa kluczowe: elektromiografia powierzchniowa,  skurcz mięśni, terapia tkanek miękkich.   Summary An electromyography is a measurement of the electrical signal connected with the myospasm. There is a housemaid regarded as the objective method for the registration of potentials of superficial muscles. Because of the repetitiveness and the comparability of examinations electrophysiological is being used in diagnostic proceedings and controlling the course of disease and the effectiveness of the treatment. Presenting the literature review was a purpose of our work. This examinations are demonstrating the surface electromyography is useful in the objective assessment of effectiveness of therapy of soft tissues.   Key words: surface electromyography, a cramp, therapy of soft tissues.